NON FORMAL EDU ROLE ANALYSIS IN IMPROVING THE MARGINAL' S QUALITY IN MILENIAL PERIODE - Endang Sondari (CV. Bunda Ratu, 2024)
Education in Indonesia should receive special attention. This is because there are still many people in the community who have not received a good education, such as the marginalized. Many of them drop out of school due to unsupportive family finances. For this reason, both the government and the private sector are trying to build non-formal schools, such as PKBM. This research is a research on non-formal education for the marginalized. The object of this research is PKBM Bintang Kita - Bandorasa Kulon, which is located in Kuningan, Jawa Barat. This study aims to describe the implementation of culture-based PKBM learning, by describing the process of implementing activities, supporting factors and inhibiting PKBM factors. This research uses descriptive qualitative method, with observation, documentation and interview techniques. The result of this research is the implementation of PKBM Bintang Kita Bandorasa Kulon as a non-formal school for the welfare of marginalized communities. In addition, the results of this study are about the technique used by PKBM Bintang Kita Bandorasa Kulon, so that it gets a positive response from the marginalized